(untitled) (Journal of Geography and Environmental Management, 2017)
The article examines the experience of China and Kazakhstan in the implementation of renewable (green) energy for sustainable development, the main problems and ways to solve them. In the modern world, energy is the basis for the development of basic industries that determine the progress of social production. The purpose of searching for alternative energy sources is the need to get it from the energy of renewable or almost inexhaustible natural resources. At the present stage of development, green energy depends on the interconnected development of such areas as renewable energy sources, energy saving, resource saving and waste management. The energy potential of Kazakhstan is compared with the People’s Republic of China. The significant potential of Kazakhstan in energy saving has been underestimated to the present time, the focus in the current policy has been made on the development of power capacities. The development of energy technologies is very important for the future of all mankind. Availability of energy available for consumption has always been necessary to meet human needs, increase the duration and improve the conditions of his life. Based on the results of the analytical review, recommendations were developed to achieve the set goals for the introduction of alternative energy in the sustainable development of Kazakhstan.